Autoimmune thyroiditis in young and old mice: differential effect of high doses of PHA. - Esquivel, P O (1982)
Experimental autoimmune thyroiditis (EAT) was used to study the effect of age and PHA in the autoimmune response. EAT was induced in mice by two injections 7 days apart of soluble syngeneic mouse thyroglobulin (MTg) and lipopolysaccharide (LPS) as adjuvant. Thereafter the antibody titre to MTg was determined in the serum and the degree of cellular infiltration estimated in thyroid sections. The results show that in old mice the humoral response is low and no cellular infiltration is found in the thyroid; young mice showed both types of immune response. Phytohaemagglutinin (PHA) was shown to inhibit antibody production when given before the first and second antigen injection, and to suppress completely the cellular immunity against thyroid tissue. When given to old mice a reduction in anti-MTg titre is also seen, but no effect on infiltration is found. However when PHA is only given before the second dose of antigen a stimulation of cellular immunity is seen in contrast to young mice where there is no effect.